Toxicity of rare earth elements: An overview on human health impact - Brouziotis, Antonios Apostolos; Giarra, Antonella; Libralato, Giovanni; Pagano, Giovanni; Guida, Marco; Trifuoggi, Marco (Frontiers in Environmental Science, 2022)
Rare earth elements (REEs) are metals including the 15 lanthanides together with Yttrium and Scandium. China is the leading country in their exploitation and production (~90%). REEs are necessary for the production of several technological devices. This extended use of REEs has raised concerns about human health safety. In this review, we investigated the hazard of REEs to human health and the main gaps into the knowledge like as the need to develop further focused research activity. We categorized the research papers collected into eight main sections: environmental exposure, association of REEs with health problems, exposure to REEs due to lifestyle, REE exposure through the food chain, Gd contrast agents causing health problems, occupational REE exposure, and cytotoxicity studies of REEs. This review provided information about the exposome of REEs (the exposure of REEs to the human body), the existing research data, and the gaps that require attention and must be further investigated. More than one third of the literature about REE toxicity to human health concerns their cytotoxicity to human cell lines, while hair, blood serum and blood are the most studied matrices. The main results evidenced that REEs can enter human body via several routes, are associated with numerous diseases, can cause ROS production, DNA damage and cell death, and are more toxic to cancer cells than normal cells.